Diversity of Butterfly Species (Subordo Rhopalocera) in Kerandangan Natural Tourism Park as High School Biology Enrichment Material - Alawiyah, Rita; Santoso, Didik; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Butterflies belong to the order Lepidoptera and have the highest biodiversity in Indonesia. Butterflies have many important values in life, such as maintaining ecosystem balance and enriching biodiversity. Kerandangan Nature Tourism Park includes a butterfly habitat located in Kerandangan Hamlet, Senggigi Village, Batu Layar District, West Lombok Regency. The aim of this research is to determine the diversity of butterfly species in the Kerandangan Nature Tourism Park, West Lombok Regency as enrichment material for high school biology lessons. The method used was exploratory descriptive with 4 data collections in October-November 2023. Data collection used a survey method with a sweep net technique and followed three predetermined observation routes, namely the intensive use block, protected block and rehabilitation block. Next, the data was analyzed using the diversity index, dominance index and evenness index. The research results found 262 individuals consisting of 3 families (Papilionidae, Nymphalidae, Pieridae), from 23 species. The butterfly diversity index of 3,069 is included in the high category. The diversity index on the 3 routes is in the medium category, namely the intensive use block is 2.96, the protected block is 2.77, and the rehabilitation block is 2.75. Information related to the diversity of butterflies in the Kerangan Nature Tourism Park can be used as enrichment material in high school biology learning.